Odrębna własność lokali - zagadnienia sporne: [Separate ownership of premises - contentious issues] (Studia Prawnicze / The Legal Studies, 1991)
W razie wyodrębnienia własności lokali mieszkalnych wszelkie części domu, które nie służą wyłącznie do użytku właścicieli poszczególnych lokali, oraz grunt, na którym został wzniesiony dom, stanowią współwłasność właścicieli lokali (art. 136 § 1 k.c.). Jak na to wskazuje przepis art. 137 § 2 pkt 2 k.c., jest to współwłasność w częściach ułamkowych, stanowiąca prawo związane z własnością lokalu (art. 136 § 2 zd. 1 k.c.). Współwłasność tę - ze względu na treść art. 136 § 2 zd. 2 k.c. - określa się jako współwłasność przymusową. Analiza wymienionych przepisów pozwala na wniosek, że istnienie wspólnej nieruchomości stanowi konieczną przesłankę odrębnej własności lokali. In the case of separate ownership of residential dwellings, all parts of the house which are not exclusively used by the owners of the individual dwellings, as well as the land on which the house has been erected, are jointly owned by the owners of the dwellings (Article 136(1) of the Civil Code). As indicated by the regulation of Article 137(2)(2) of the Civil Code, it is a joint ownership in fractional parts, comprising a right connected to the ownership of the premises (Article 136(2) sentence 1 of the Civil Code). This joint ownership - in light of the wording of Article 136(2), sentence 2 of the Civil Code - is referred to as forced joint ownership. An analysis of the aforementioned provisions allows the conclusion that the existence of a shared property is a necessary prerequisite for the separate ownership of premises.